Transethosomes as Vesicular Drug Delivery : a Modified Form of Ethosomes and Transfersomes - Rosmiati, Meiti; Wulantresna, Dewi; Emelia, Rida (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Liposomal vesicle formulations can be classified into two categories, namely rigid hard vesicles such as liposomes and elastic vesicles such as transferosome. One of the shortcomings of conventional liposomes is their permeation strength in the stratum corneum, so that in later generations liposomes are designed to be able to better overcome these obstacles. Deformable liposomes, also known as transfersomes, are liposomes that contain edge activators/surfactants. The combination of phospolipids with membrane softening agents allow the transfersome to penetrate pores that are five times smaller than their own diameter, even after it passes through small pores. Ethosomes are liposomes with modified ethanol that act as reservoir systems and offer the continuous delivery of drugs to the desired site. The high concentration of ethanol content in the manufacture of ethosome systems makes this system different from other vesicle systems, because the ethanol content will interfere with the double layer of skin lipids and thus increase the ability of vesicles to penetrate into the stratum corneum. Phospholipids in ethosomes serve as vesicular-forming components. Phospholipids are also reported to act synergistically with ethanol to improve drug permeation in ethosome formulations. Transethosomes are ethanol-based lipid vesicular systems resulting from modifications of ethosome and transfersome systems that can increase penetration in the skin. It is a new generation of the ethosome system which developed by increasing the flexibility of vesicles by redistributing edge activators and lipids on the skin. The mechanism of action of transethosomes is a combination of advantages of both transferosome systems and ethosomes.